THE ASSESSMENT OF CITARUM RIVER WATER QUALITY IN MAJALAYA DISTRICT, BANDUNG REGENCY - Finna Fitriana; Doddi Yudianto; S Sanjaya; Andreas F V Roy; Yong Chan Seo (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
Citarum River is one of the biggest rivers in Java Island and the primary source of Jakarta's water supply. Named the dirtiest river globally in 2013, the Indonesian government is committed to improving the Citarum River's water quality by 2025. However, the Majalaya District, the center of the textile industry area in the upstream part of the Citarum River, is indicated to have significantly contributed to the river pollution. Hence, it is essential to conduct a study to evaluate the water quality in the Citarum River, especially in the Majalaya District. The results showed a considerable decrease in water quality from upstream to downstream of the Citarum River in 2013-2021. Concurrently, it was also found that the factory effluent far exceeded the permissible limit.